ANALYSIS OF THE IMPACT OF COVID-19 ON SOCIAL CHANGE IN COASTAL COMMUNITIES IN DUSUN X VILLAGE: GENDER PERSPECTIVE - Adawiyah, Azzahra Al; Siahaan, Dyva Patricia; Zuhra, Fifia El (Journal of Gender and Social Inclusion in Muslim Societies, 2024)
This research aims to investigate the impact of the COVID-19 pandemic on social change among coastal communities in Celawan Village, Dusun X, Pantai Cermin District, Serdang Berdagai Regency, North Sumatra Province. This research uses a qualitative approach with descriptive methods to explore social changes, including people's values, attitudes and behavior patterns after the pandemic. The research was conducted in the period November 2020 to January 2021. The total sample in this study was 30 respondents who were selected purposively. The sampling technique was carried out by considering variations in age, gender and educational background. Data was collected through in-depth interviews with selected sources. Data analysis was carried out through a process of interview transcription, thematic coding, and identification of emerging patterns of social change. Using this method allows researchers to understand in depth how the COVID-19 pandemic has affected the social dynamics of coastal communities. The research results show that the pandemic has induced significant social changes in coastal communities, including adaptation to new conditions, adjustments to economic needs, and adoption of new habits to maintain health and safety. These changes are influenced by various internal and external factors. This research provides valuable insight into how the COVID-19 pandemic has shaped social dynamics in coastal communities, as well as providing a basis for further understanding of future adaptation and mitigation strategies in the face of similar challenges. Keywords for this research include social adaptation, COVID-19, coastal communities, behavior change, and North Sumatra.